The effect of demographic characteristics on employment in Sub- Saharan Africa. (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2021)
This study aimed at establishing the effect of demographic characteristics on employment in Sub Saharan Africa.  The study used data ranging from the year 1990 to the year 2015 that was obtained from the data banks of World Bank and FAOSTAT. The panel data that was obtained and used was for 30 Sub-Saharan African Countries. The traditional Neo classical production function was utilized in this study in estimating the regression results. Hausman test was carried out and it determined that fixed effects estimations were preferred to random effects and as a consequence, random effects estimations were made use of during the analysis of data. In establishing the relationship between demographic characteristics and employment, demographic characteristics, imports and services sectors variables were found to statistically and significantly influence employment. However, domestic capital was found to negatively influence employment though this was not statistically significant, while exports was found negatively and statistically significantly influencing employment.